Twenty-first century knowledge mapping on oral diseases and physical activity/exercise, trends, gaps, and future perspectives: a bibliometric review - Gomes, Thamires Campos; Gomes Moura, José Lucas; Baia-da-Silva, Daiane Claydes; Lima, Rafael Rodrigues; Rodrigues, Patrícia de Almeida (Frontiers in Sports and Active Living, 2024)
Maintenance and improvement of an individual's overall well-being require a multidisciplinary approach that encompasses everything from oral health care to regular physical exercise. The notion that poor oral health can influence general health and athletic performance has sparked an interest in this relationship. This study offers an overview of relevant research and a knowledge map,and discusses publication metrics and key topics concerning the relationship between physical activity or exercise and oral diseases. We searched the Web of Science database for articles published in the 21st century that addressed the relationship between physical activity and oral diseases. Under the stipulated inclusion criteria, a rigorous selection process yielded 276 from 3,883 retrieved articles. The articles were classified by what was assessed as follows: occurrence of oral diseases in athletes or sports enthusiasts (n = 174); impact of physical activity or exercise on the oral cavity (n = 59); effects of oral changes on sports performance and physical fitness (n = 31); and the connection between oral health status, physical activity or exercise, and systemic conditions (n = 12). Orofacial trauma has received the most attention among all investigated oral diseases. However, there is a need for greater attention of dysfunctional habits that can contribute to premature tooth wear, as well as oral inflammatory diseases that can have systemic implications. This mapping can encourage the development of new primary research.